1990
DOI: 10.1104/pp.93.1.166
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Carbon Partitioning to Respiration during Dark Ammonium Assimilation by the Green Alga Selenastrum minutum

Abstract: The assimilation of NH4 causes a rapid increase in respiration to provided carbon skeletons for amino acid synthesis. In this study we propose a model for the regulation of carbon partitioning from starch to respiration and N assimilation in the green alga Selenastrum minutum. We provide evidence for both a cytosolic and plastidic fructose-1,6-bisphosphatase. The cytosolic form is inhibited by AMP and fructose-1,6-bisphosphate and the plastidic form is inhibited by phosphate. There is only one ATP dependent ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
87
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 74 publications
(94 citation statements)
references
References 42 publications
7
87
0
Order By: Relevance
“…7), a potent activator of S. minutum PK, thus reinforcing its activation. This hypothesized mechanism for activation of PK and PFK following a transition to anaerobiosis is similar to that described for activation of glycolysis to provide carbon skeletons for NH4' assimilation (38).…”
Section: 04mentioning
confidence: 70%
See 3 more Smart Citations
“…7), a potent activator of S. minutum PK, thus reinforcing its activation. This hypothesized mechanism for activation of PK and PFK following a transition to anaerobiosis is similar to that described for activation of glycolysis to provide carbon skeletons for NH4' assimilation (38).…”
Section: 04mentioning
confidence: 70%
“…The physiological concentrations of metabolite effectors of PK and PFK have been shown to be in the range to effect enzyme activity (38). Also, recent work has suggested that the in vivo activity of S. minutum PK may be limited by the availability of ADP (38). Based on this information and on examination of short-term metabolite changes following a transition to anaerobiosis, we are able to hypothesize the following mechanism for the activation of PK and PFK.…”
Section: 04mentioning
confidence: 90%
See 2 more Smart Citations
“…FCCP treatment approximately doubled the respiration rate (O 2 consumption) of the cells (data not shown), indicating that it had been restricted by the availability of ADP (Dry et al, 1987). The increased availability of ADP after FCCP addition might be expected to decrease the reduction state of the mitochondrial pyridine nucleotide pool (Neuburger et al, 1984;Day et al, 1987) and result in the activation of pyruvate kinase, causing an increase in pyruvate (Turpin et al, 1990;Plaxton, 1996). While the more oxidized pyridine nucleotide pool expected in the presence of FCCP would not favor AOX reduction (Vanlerberghe et al, 1995), the expected increase in pyruvate would favor the reduced form and may explain why FCCP brought about no significant change in the AOX protein form (Fig.…”
Section: Discussionmentioning
confidence: 99%